Debated issues in sovereign predestination early lutheran predestination, Calvinian reprobation, and variations in Genevan lapsarianism - Beeke, Joel R. 1952-; Vandenhoeck & Ruprecht (Göttingen Bristol, CT Vandenhoeck & Ruprecht, 2017)
"Joel R. Beeke examines three flashpoints of controversy in Reformation and Post-Reformation theology: first, the development of the Lutheran doctrine of predestination from Martin Luther and Philip Melancthon to the Formula of Concord; second, the doctrine of repbrobation as traced through the writings of John Calvin; and third, the doctrine of predestination in Geneva from Theodore Beza in the sixteenth century to Jean-Alphonse Turretin and Jacob Vernet in the eighteenth century. This books offers a balanced, historical analysis of a difficult subject." -- From back of book
Predestination in early Lutheranism -- Reprobation in Calvin's theology -- Lapsarian variations among later Genevan theologians
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Predestination -- History of doctrines; Reprobation -- History of doctrines; Fall of man; Lutheran Church -- History of doctrines; Calvinism -- History of doctrines